Virtual learning environments – help or hindrance for the ‘disengaged' student? - Alice Maltby; Sarah Mackie (Association for Learning Technology, 2009)
The introduction of virtual learning environments (VLEs) has been regarded by some as a panacea for many of the problems in today's mass numbers modular higher education system. This paper demonstrates that VLEs can help or hinder student engagement and performance, and that they should be adapted to the different types of learner. A project is described that aimed to investigate whether the introduction of a VLE can assist ‘disengaged' students, drawing on click count tracking data and student performance. The project took place in the context of two very large undergraduate modules (850 and 567 students) in a Business School of a new university in the UK. In an adaptation of a model of learner engagement in Web-enhanced environments, four distinct learner types have emerged: model, traditionalist, geek and disengaged. There was evidence that use of the VLE exacerbated, rather than moderated, the differences between these learner types.